2021
DOI: 10.1186/s12951-021-01115-9
|View full text |Cite
|
Sign up to set email alerts
|

MCP mediated active targeting calcium phosphate hybrid nanoparticles for the treatment of orthotopic drug-resistant colon cancer

Abstract: Background Colon cancer is a most common malignant cancer in digestive system, and it is prone to develop resistance to the commonly used chemotherapy drugs, leading to local recurrence and metastasis. Paris saponin VII (PSVII) could not only inhibit the proliferation of colon cancer cells but also effectively induce apoptosis of drug-resistant colon cancer cells and reduce the metastasis of drug-resistant colon cancer cells as well. However, PSVII was insoluble in water and fat. It displayed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The drug release profile was pH-dependent and responsive to the colonic microenvironment, showing a preferential distribution in the colon [ 187 ]. A form of PEC (the modified citrus pectin) that is able to bind galectin-3 and is highly expressed on the membranes of colon cancer cells was exploited to functionalize calcium phosphate NPs [ 188 ] and CS NPs [ 189 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug release profile was pH-dependent and responsive to the colonic microenvironment, showing a preferential distribution in the colon [ 187 ]. A form of PEC (the modified citrus pectin) that is able to bind galectin-3 and is highly expressed on the membranes of colon cancer cells was exploited to functionalize calcium phosphate NPs [ 188 ] and CS NPs [ 189 ].…”
Section: Resultsmentioning
confidence: 99%
“…The enrichment of colonic flora and specific enzymes plays an important role among the strategies for targeted drug delivery to the gut due to their ability to selectively degrade materials. For this reason, polysaccharides such as pectin, inulin, and some natural gums, which can resist the passage through the gastric tract but are degraded by the intestinal microbiome, were largely used as nanocarriers [ 127 , 184 , 187 , 188 , 189 , 196 , 197 ]. Drug release based on resident bacteria seems to represent a common strategy, although the inflammatory condition related to several gut pathologies, especially when associated with severe diarrhea, can affect the composition of gut microflora [ 340 ].…”
Section: Discussionmentioning
confidence: 99%
“…A pectin gel prepared by mixing a heated pectin solution and a frozen calcium chloride solution induced a 4.8 ± 0.7 haemolysis rate [ 19 ]. Many other studies have previously shown good haemocompatibility for pectin-based biomaterials [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scanning electron microscope results showed that the nanoparticles had small particle size (<50 ​nm), and the mixed nanoparticles of heparin/CaCO 3 /CaP loaded with doxorubicin could better solve the drug resistance of tumor cells. Similarly, PSVII carboxymethyl-β-cyclodextrin inclusion compound was successfully encapsulated in colon cancer targeting calcium phosphate nanoparticles (PSVII@MCP-CaP) by using modified citrus pectin as stabilizer agent and colon cancer cell targeting moiety [ 75 ].…”
Section: Application Of Calcium Phosphate Nanocarriersmentioning
confidence: 99%